A Paradigmatic Study to Legally Assess the Authority and Right of Jurisdiction of Public Sector Governance: Examining Discretion in Government Administrative Law - Gultom, Tasman; Indarti, Erlyn; Sa’adah, Nabitatus (International Journal of Criminology and Sociology, 2021)
This study aims to explore how government administration has so far been carried out within the authority framework of discretion owned by government agencies. This study uses a qualitative method with a descriptive normative analysis approach to obtain a paradigmatic study as a legal assessment to investigate the authority and right of jurisdiction of public sector governance. The focal point was to examine discretion in government administrative law as contained in Law No. 30 of 2014 about Government Administration. The results showed that as a freedom of thought and action in legalization, discretionary authority lies in the authority to carry out positions held by government administrative officials. The results also highlight that discretion is still rigid in its application in Indonesia because the procedure to perform this discretion is tiered. The theoretical implication revealed that the difference has led to controversy between scientific discretion and the discretion contained in the Law on Government Administration, decreasing public official’s willingness to do something for the benefit and welfare of society and seekers of justice.